Directions of development of time management skills of higher education students in the process of professional training - Vorobieva, Yevheniia (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article highlights the peculiarities of developing time management skills for modern professionals. It is also analyzed that success in educational activities depends on successful time planning by students. The basic concepts on which the use of time planning technologies is based are defined. The article contains the author's own interpretation of the directions of development of time management skills in higher education students in the process of professional training.

Висвітлено особливості розвитку навичок тайм-менеджменту для сучасних фахівців. Також проаналізовано, що успішність в навчальній діяльності залежить від вдалого планування часу студентами. Визначено базові концепції, на яких ґрунтується застосування технологій планування часу. Стаття містить авторське трактування напрямів розвитку навичок тайм-менеджменту у здобувачів вищої освіти в процесі професійної підготовки.
Напрями розвитку навичок тайм-менеджменту у здобувачів вищої освіти в процесі професійної підготовки
Keywords: time management; time management skills; development of time management skills; students; professional training; тайм-менеджмент; навички тайм-менеджменту; розвиток навичок тайм-менеджменту; здобувачі освіти; професійна підготовка